Характеристика сучасного стану міжгалузевих відносин в агропромисловому комплексі - Томілін, О.О. (Економіка промисловості, 2012)
Проаналізовано сучасний стан та перспективи розвитку міжгалузевих відносин в агропромисловому комплексі. Виконано аналіз основних галузей сільськогосподарського виробництва та міжгалузевих зв’язків аграрної сфери економіки. Запропоновано можливі шляхи вирішення проблеми міжгалузевого обміну.
Ключові слова: міжгалузеві відносини, сільськогосподарське підприємство, виробництво, міжгалузевий обмін, агропромисловий комплекс. Проанализировано современное состояние и перспективы развития межотраслевых отношений в агропромышленном комплексе. Проведен анализ основных отраслей сельскохозяйственного производства и межотраслевых связей аграрной сферы экономики. Предложены возможные пути решения проблемы по межотраслевому обмену.
Ключевые слова: межотраслевые отношения, сельскохозяйственное предприятие, производство, межотраслевой обмен, агропромышленный комплекс. The article examines the current situation and development prospects of inter-branch relations in the agro-industrial complex. The analysis of basic branchesof agricultural production and inter-branch connections of agrarian sphere of economy is made. The grounds are given for the basic types of agricultural equipment at agricultural enterprises.
The necessity of inter-branch exchange is shown in the article. The inter-branch relations are of crucial importance in the spheres of processing, storage and sales of final agricultural products. The article proves that the main mechanism of agro-industrial production improvement and corresponding synergetic effect achievement is the focus of the vertical type production integration. The vertical integration provides unity and continuity of supporting and technological actions and it uses the complex economic resources to the best advantage.
The possible ways of the inter-branch exchange problem solution are offered.
Keywords: inter-branch relations, agricultural enterprise, production, inter-branch exchange, agro-industrial complex.